Antidiabetic Effect of Noni Fruit and Moringa Leaves Extract on Blood Glucose Level, Hepatic and Pancreatic Histological Features of Diabetic Mice - Utomo, Ratno Tri; Christyaningsih, Juliana; Rahmawati, Hanifa; Meidayana, Ema; Wulandari, Meisa; Oktavianingsih, Yulis; Andriyani, Nurul (Jurnal Kesehatan, 2023)
One of the chronic diseases with high blood glucose levels is a characteristic of Diabetes Mellitus. Utilization of herbal ingredients needs to be developed to reduce blood sugar levels in diabetes, and one of them is by using moringa leaf extract and noni fruit. This study aimed to analyze the effect of a combination of moringa leaf extract and noni fruit on blood glucose levels and tissue cytology in diabetic mice. The study was a randomized pretest-posttest control group design using 28 male mice divided into seven groups. The data analysis showed the lowest decrease in blood glucose levels in the group of diabetic mice given noni fruit and moringa leaf extract at a dose of 150mg/20g BW/oral/day for two weeks. The results of histological examination of liver and pancreas tissue showed no tissue is damaged.